L’EDUCAZIONE DELLE RAGAZZE NEL XIV SECOLO SECONDO FRANCESCO DA BARBERINO - Głusiuk, Anna (Saeculum Christianum. Pismo Historyczne, 2017)
Francis from Barberino is an author of one of the few female etiquette texts composed in the Middle Ages. In this period, writers wrote some texts about dress etiquette but the most of them was dedicated to the male reader and there are only some text written for women. In his works, Barberino shows the dress etiquette appropriate for a girl at the age of marriage coming from a family of high social status. Thanks to his work, it is possible to see which virtues was appreciated, what was allowed and which behaviors was not accepted by the society of that time.